Community economic empowerment through oyster mushroom cultivation: A case study on agricultural-based empowerment using local raw materials - Rohmah, Isyfi Shofia; Sholikhah, Amirotun (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Community economic empowerment based on oyster mushroom cultivation is one alternative to improve the welfare of rural communities. The potential for abundant raw materials, such as sawn timber waste, as well as the relatively easy cultivation process and low capital, make this business promising. The Sumber Maju Business Group seeks to implement empowerment through training and business development to improve the economy of the villagers. Methods: This research uses a qualitative approach with a case study method to analyze the implementation of economic empowerment through oyster mushroom cultivation by the Sumber Maju Business Group. Data were collected through in-depth interviews with administrators, group members, and the local community, as well as through observation of the empowerment stages carried out, from preparation to evaluation and termination. Findings: This study found that community empowerment through oyster mushroom cultivation succeeded in improving the village economy, as evidenced by the increasing number of mushroom huts and group members' income. However, some stages of empowerment are still not optimal, such as the lack of government involvement in providing the necessary production equipment and the low awareness of some people about the potential of this business. Nevertheless, there is a strong desire from the community to develop this business further. Conclusion: Economic empowerment through oyster mushroom cultivation can increase the economic independence of group members and improve community welfare. However, there are challenges related to government involvement and the provision of adequate production facilities. Novelty/Originality of this article: This article offers new insights into agricultural-based economic empowerment that utilizes affordable local potential, namely wood waste, as the main raw material.